Nitrous oxide emissions from tea garden soil following the addition of urea and rapeseed cake - Yu, Jialuo; Lin, Shan; Shaaban, Muhammad; Ju, Wenliang; Fang, Linchuan (Journal of soils and sediments, 2020)
Purpose Tea gardens, being a key agroecosystem type, are an important source of nitrous oxide (N 2 O) emissions. However, main factors that regulate N 2 O emissions following urea and organic matter amendments have yet to be clarified. Materials and methods To investigate the influence of different fertilization management measures on N 2 O emissions in tea garden soil, a 50-day laboratory incubation experiment was conducted. Five treatments were designed for this experiment: control (CK), urea (U), rapeseed cake (R), urea + rapeseed cake (2:1, UR1), and urea + rapeseed cake (1:2, UR2). Results and discussion N 2 O emission flux in the R treatment peaked at 14.12 μg kg −1 h −1 on day 19, which occurred later than the UR1, UR2, and U treatments. Cumulative N 2 O emissions from the R and UR2 treatments were 6073 and 4296 μg kg −1 , respectively, which were greater by a factor of 11.2 and 7.9, respectively, compared to the U treatment. Moreover, N 2 O emissions of the UR1 and UR2 treatments were significantly lower than the R treatment. Additionally, N 2 O emissions were also significantly positively correlated to pH levels and microbial biomass carbon (MBC) content. MBC content had the most direct and greatest influence on soil N 2 O emissions, indicating that MBC could be the key limiting factor for N 2 O emissions in this experiment. Conclusions A single application of rapeseed cake caused an increase in N 2 O emissions, whereas the combined application of rapeseed cake and a synthetic N fertilizer (urea) caused a decrease in N 2 O emissions. Results from this study offer potential strategies to mitigate soil N 2 O emissions from tea garden agroecosystems through improved field fertilization management.